Bankruptcy Risk Models for Polish SMEs – Regional Approach - Ptak-Chmielewska, Aneta (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Credit risk management is a key element in bank management. For credit risk management, statistical models are used, the so‑called scoring and rating models. For enterprise risk assessment, rating models are used. Rating models consist of quantitative models (based on financial ratios) and qualitative models (based on a questionnaire). For estimation of quantitative models, econometric and statistical models are used, mainly logistic regression models. In this paper, statistical models for quantitative assessment are presented, including an empirical example based on the sample of data for SMEs made available by one of Polish banks. A logistic regression model with a nominal variable – the region of activity, including territorial differences, was used. The construction of rating model was presented, including the sector and region of activity.